Charles Ives's Concord : essays after a sonata - Gann, Kyle (Music in American life., 2017)
In 1921, insurance executive Charles Ives sent out copies of a piano sonata to two hundred strangers. Laden with dissonant chords, complex rhythm, and a seemingly chaotic structure, the so-called Concord Sonata confounded the recipients, as did the accompanying book, Essays before a Sonata . Kyle Gann merges exhaustive research with his own experience as a composer to reveal the Concord Sonata and the essays in full. Diffracting the twinned works into their essential aspects, Gann lays out the historical context that produced Ives's masterpiece and illuminates the arguments Ives himself explored in the Essays . Gann also provides a movement-by-movement analysis of the work's harmonic structure and compositional technique; connects the sonata to Ives works that share parts of its material; and compares the 1921 version of the Concord with its 1947 revision to reveal important aspects of Ives's creative process. A tour de force of critical, theoretical, and historical thought, Charles Ives's Concord provides nothing less than the first comprehensive consideration of a work at the heart of twentieth century American music.